2019
DOI: 10.1007/s10896-019-00036-4
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Physical Abuse & Exposure to Parental IPV on Young Adolescents in Poland: a Clinical Assessment and Comparison of Psychological Outcomes

Abstract: This study explores characteristics of youth who experienced domestic violence in Poland. Specifically, young adolescents who were victims of physical abuse perpetrated by parents and young adolescents who were exposed to parental intimate partner violence (IPV) were studied to determine whether the groups had similar or different psychological outcomes. Additionally, the study looked into ways by which these youth cope with stress and demonstrate self-efficacy. Data were collected from 90 youth aged 11 to 14 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
13
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 55 publications
1
13
0
2
Order By: Relevance
“…The association between parental IPV exposure and delinquent behavior in elementary and adolescent children is not as clear as it is because research results are often not consistent. For example, both boys and girls who have been subjected to parental IPV have engaged in more delinquency (Rode et al, 2019) and rule-breaking behaviors than non-exposed youths, even though boys are more likely to have committed violent property or felony offenses (Fong et al, 2017). Some of these adolescents used to externalize their negative feelings, and as a result, they developed significant issues (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The association between parental IPV exposure and delinquent behavior in elementary and adolescent children is not as clear as it is because research results are often not consistent. For example, both boys and girls who have been subjected to parental IPV have engaged in more delinquency (Rode et al, 2019) and rule-breaking behaviors than non-exposed youths, even though boys are more likely to have committed violent property or felony offenses (Fong et al, 2017). Some of these adolescents used to externalize their negative feelings, and as a result, they developed significant issues (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Many studies have been conducted to examine the association between domestic violence exposure and internalizing symptoms like anxiety and depression (Alaggia & Donohue, 2018; Carracedo et al, 2018; Pingley, 2017; Rode et al, 2019). Longitudinal studies have shown that exposure to domestic violence has long-term and lasting impacts on internalizing symptoms.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Rode, D., Rode, M., Marganski, A.J. указывают, что часто именно изоляция становится определяющим для формирования посттравматического стрессового расстройства [1]. Both L.M, Favaretto T.C.…”
unclassified